Air Pollution: Sources, Impacts and Controls 2018
DOI: 10.1079/9781786393890.0113
|View full text |Cite
|
Sign up to set email alerts
|

Impact of air pollution on the environment and economy.

Abstract: It is the predicament of mankind that man can perceive the problematique, yet, despite his considerable knowledge and skills, he does not understand the origins, significance, and interrelationships of its many components and thus is unable to devise effective responses. This failure occurs in large part because we continue to examine single items in the problematique without understanding that the whole is more than the sum of its parts, that change in one element means change in the others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…The impact of air pollution ( and ) is indirect as it stems from its contribution to biodiversity decline ( 166 ), which in turn has been argued to increase human exposure to zoonotic pathogens ( 167 ). Moisture resulting from precipitation ( ) results in dense vegetation that provides suitable conditions for vector proliferation ( 168 ).…”
Section: Results and Discussion: A Case Study In The Valencian Commun...mentioning
confidence: 99%
“…The impact of air pollution ( and ) is indirect as it stems from its contribution to biodiversity decline ( 166 ), which in turn has been argued to increase human exposure to zoonotic pathogens ( 167 ). Moisture resulting from precipitation ( ) results in dense vegetation that provides suitable conditions for vector proliferation ( 168 ).…”
Section: Results and Discussion: A Case Study In The Valencian Commun...mentioning
confidence: 99%
“…According to European Environment Agency (EEA, 2022) key primary air pollutants are particulate matter (PM), black carbon (BC), sulphur oxides (SO 2 ), nitrogen oxides (NO x ) (including nitrogen monoxide and nitrogen dioxide, NO 2 ), ammonia (NH 3 ), carbon monoxide (CO), methane (CH 4 ). Sulfur and nitrogen are the most important air pollutants affecting the aquatic ecosystem, the source of which is largely air (Sonwani and Maurya, 2019). Air pollution (especially sulfur oxides, nitrogen oxides and ozone) affects diverse ecosystems and biodiversity by changing its physical components.…”
Section: Introductionmentioning
confidence: 99%
“…Oxides of sulfur and nitrogen react together to form acid rain and increase the acidity of the soil. Increased acidity negatively affects nutrient cycling, reproduction and climate regulation in the ecosystem (Sonwani and Maurya, 2019). The gases that trap the infrared rays coming to the world and convert them into heat by forming a layer between the atmosphere and the earth, absorb the rays reflected from the earth and regulate the heat balance of the world are called greenhouse gases (Bayraç and Emrah, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution is a significant threat to modern society, and it has been shown that it negatively affects both, the people’s health (Ghorani-Azam et al, 2016 ; Lave & Seskin, 2013 ; Shahriyari et al, 2022 ) and the environment (Saurabh Sonwani & Vandana Maurya, 2019 ; Stevens et al, 2020 ). Particulate matter (PM) with an effective aerodynamic diameter smaller than 2.5 and 10 μm (PM 2.5 and PM 10 ) have gained specific attention among air pollutants, and their effects on human health and ecosystems have become important research topics in recent years (Bodor et al, 2022 ; Faraji Ghasemi et al, 2020 ; Leão et al, 2022 ; Yunesian et al, 2019 ; Zoran et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%